Evaluation of a surface imaging system's isocenter calibration methods. (6th March 2017) - Paxton, Adam B.; Manger, Ryan P.; Pawlicki, Todd; Kim, Gwe‐Ya
Abstract: AlignRT is a surface imaging system that has been utilized for localizing and tracking patient position during radiotherapy. AlignRT has two calibration procedures that can set the system's isocenter called "Monthly Calibration" (MC) and "Isocentre Calibration" (IC). The MC utilizes a calibration plate. In addition to the calibration plate, the IC utilizes a cubic phantom that is imaged with the linac treatment beam to aid in aligning the AlignRT and treatment‐beam isocenters. This work evaluated the effects of misaligning the calibration plate during the calibration process. The plate was intentionally shifted away from isocenter ±3.0 mm in the longitudinal and lateral directions and ±1.0 mm in the longitudinal, lateral, and vertical directions. A mock stereotactic radiosurgery (SRS) treatment was used to evaluate the effects of the miscalibrations. An anthropomorphic head phantom was placed in an SRS treatment position and monitored with the AlignRT system. The AlignRT‐indicated offsets were recorded at 270°, 315°, 0°, 45°, and 90° couch angles for each intentional misalignment of the calibration plate during the MC. The IC was also performed after each miscalibration, and the measurements were repeated and compared to the previous results. With intentional longitudinal and lateral shifts of ±3.0 mm and ±1.0 mm of the calibration plate, the average indicated offsets at couch rotations of ±90° were 4.3 mm and 1.6 mm, respectively. This was in agreement with the theoretical offset of √2*(shift‐of‐the‐calibration plate). Since vertical shifts were along the rotation axis of the couch, these shifts had little effect on the offsets with changing couch angle. When the IC was applied, the indicated offsets were all within 0.5 mm for all couch angles for each of the miscalibrations. These offsets were in agreement with the known magnitude of couch walkout. The IC method effectively removes the potential miscalibration artifacts of the MC method due to misalignments of the calibration plate.